(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to ascertain the level of acknowledgement of Curry flavour for Crispy Kangkong using a survey that the respondents will answer to determine the number of ratings to calculate its acknowledgement. This research will provide us with information about the background of Crispy Kangkong, allowing us to identify the priorities of the proposed Crispy Kangkong that we may need to evaluate to fulfil the purpose of the study, which is to determine the level of acceptance of the Curry flavour that we needed to produce or improve to make it more appealing to people’s taste, eyes, etc. The researchers utilize the Descriptive research design. The sampling technique to be used in this study is Simple Random sampling. Questionnaires are distributed to gather data from the respondents. The acceptance of curry flavour in Crispy Kangkong will be the topic of this study. This might include assessing if the look, taste, aroma, and marketability are acceptable to respondents. This might include the specific taste, such as how sour, bitter, or salty it is, to alter the number of components used in the Crispy Kangkong Curry flavour. The results of the data gathered from the respondents showed that researchers discovered that six of the product performances over seven, namely the aroma, taste, attractiveness, and potential to recommend to the market, have proven that the respondents are satisfied with the product with a weighted mean between 2.51 to 3.50, with the only exception being affordability for its quality with the weighted mean of 2.32, which received neutral satisfaction. Furthermore, in terms of flavour, two of the three categories of taste, bitterness, sourness, and saltiness, have a decent rating of satisfied with a weighted mean between 2.51-3.50 and neutral for bitterness with a weighted mean of 2.32, making the Curry Flavor Crispy Kangkong acceptable in respondents’ judgments.